Periodontics in Nepal: Where Have We Reached? - Pradhan, Shaili; Koirala, Pramod Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Periodontics is that speciality of dentistry which encompasses the prevention, diagnosis, and treatment of diseases of supporting and surrounding tissues of the teeth or their substitutes; the maintenance of health, function and aesthetics of these structures and tissues; and the replacement of lost teeth and supporting structures by grafting or implantation of natural or synthetic devices and materials. The quality field of Periodontics started in Nepal after 1999. The postgraduate studies in Periodontology and Oral Implantology have been running for a decade. Specialists in significant numbers are providing services throughout the country. Scientific researches and academic activities have been organised. Nepalese Society of Periodontology and Oral Implantology (NSPOI) has become a forum that is gaining recognition in the nation and on a global scale with the successful organisation of annual conferences, annual clinical meetings, postgraduate conventions and participations in international conferences since its establishment in 2014. The journal of the society (JNSPOI) is being regularly published since 2017. Societies in India and abroad have expressed good wishes and have contributed to the society regularly.